Phenolic Acid Profiling and Antioxidant Activity of Tamarix dioica Leaves, Stem and Flowers: Antioxidant Activity of Tamarix dioica - Muhammad Qasim Samejo; Saddam Hussain Bughio; Shahabuddin Memon; Humaira Khan; Ghulam Zohra Memon; Nusrat Naeem Memon (Biological Sciences - PJSIR, 2023)
The aim of this study was to determine the phenolic acid profile and antioxidant activity of leaves, stem and flowers of Tamarix dioica. Nine compounds were identified by high performance liquid chromatography (HPLC). Overall results showed that the high content of gallic acid was detected in leaves and flowers and caffeic acid in stem. Antioxidant activity was evaluated using DPPH assay. A high antioxidant activity was observed, which is associated with very high phenolic content, indicating the potential benefit of using this species as a source of biochemical compounds.